Understanding the pay equity from the idea of universal equality in traditional Chinese philosophy - Cui, Yuanjun (Frontiers in Psychology, 2022)
Equal pay for equal work as a social behavior reflects a certain kind of social attitude. Therefore, the research on the equal pay for equal work concept should not only focus on the perspectives of law, economics and sociology, but also explore the underlying social and psychological mechanism from the perspective of social psychology, so as to gain a deeper understanding about the social psychological background, as well as the cognitive concepts and value ideals of this social behavior. Meanwhile, it is also necessary to seek its theoretical basis and support in the philosophical sense. Chinese traditional philosophy contains a profound idea of universal equality, which is mostly emphasized by the Taoist philosophy (relying on “Tao” as the theoretical basis). Centering on the relationship between Tao and all things, the Taoist philosophy demonstrates that all things in the universe, including human beings, are equal and should be treated equally. The idea of universal equality is inherently compatible with the cognitive concept and value pursuit advocated by the equal pay for equal work concept, and therefore may provide a philosophical basis and social psychological support to this social behavior.